Executive Functioning and Depressive Symptoms After Cancer: The Mediating Role of Coping. Issue 3 (April 2021) - Radin, Arielle; Ganz, Patricia A.; Van Dyk, Kathleen; Stanton, Annette L.; Bower, Julienne E.
Abstract : Supplemental digital content is available in the text. ABSTRACT: Objective: Cognitive difficulties are a common complaint among patients with breast cancer and may adversely affect psychological well-being. In particular, problems with executive functioning (EF) may interfere with coping, which is known to influence depressive symptoms. The current study was designed to examine correlations between EF, coping, and depressive symptoms in breast cancer survivors and to longitudinally test the hypothesis that coping mediates the relationship between EF and depressive symptoms. Methods: Participants included 171 women with early-stage breast cancer assessed at the end of primary treatment with surgery, radiation, and/or chemotherapy and at 6 months, 1 year, and 2 years after treatment follow-ups as part of the Mind-Body Study. Participants completed questionnaires to assess subjective EF, approach and avoidant coping, and depressive symptoms, and neuropsychological testing was conducted to assess objective EF. Bivariate correlations were used to examine associations between EF, coping, and depressive symptoms. Mediation analyses were conducted using a bootstrapping approach (PROCESS). Results: At 1 year after treatment, objective and subjective EFs were correlated with avoidant coping ( r = −0.172 [ p = .024] and r = 0.297 [ p < .001], respectively). In longitudinal analyses, use of the avoidant strategy behavioral disengagement at 1 year mediated the association between objective (95% bootstrap confidence interval = −0.282 to −0.042) and subjective (95% bootstrap confidence interval = 0.020 to 0.254) EFs at 6 months and depressive symptoms at 2 years. Conclusions: This study highlights how problems with EF during survivorship are associated with avoidant coping and depressive symptoms. Thus, these findings identify potential cognitive and affective targets for depression intervention in this population.